Analysing the language of discourse communities - Cutting, Joan (Elsevier, 2000)
This text describes how the language used in social interaction evolves from the time the speakers first meet and becomes the in-group code of a given discourse community (in this case the academic community). Most studies reported in the literature of the language of groups and intimates until now have been global, imprecise or unsystematic, and have described the language as a product at a given time; no systematic study appears to have been carried out to follow through the interactions of individuals as they form a group, to discover precisely how and why language changes over time as assumed knowledge grows. Here, the author focuses on the precise changes that occur with increasing knowledge over time, and uses a longitudinal approach to describe the language as a process.